High‐Resolution, Flexible, and Full‐Color Perovskite Image Photodetector via Electrohydrodynamic Printing of Ionic‐Liquid‐Based Ink. (18th April 2021) - Wang, Qilu; Zhang, Guannan; Zhang, Hanyuan; Duan, Yongqing; Yin, Zhouping; Huang, YongAn
Abstract: Direct full‐color image photodetectors without dichroic prisms or sophisticated color filters have considerable advantages in target recognition and information acquisition for electronic eyes and wearable sensors. However, the ability to combine various multispectral semiconductors in a high‐resolution and cost‐effective manner is still challenging. Here, high‐resolution electrohydrodynamic (EHD) printing, together with ionic liquid methylammonium acetate (MAAc) as the solvent, is first introduced to directly integrate various spectral‐response perovskite films into a pixelized full‐color photodetector. EHD printing enables micro/nanopatterning by using high electrical force to induce jetting, and MAAc improves film quality with scant pinholes and large‐size grains by decreasing the perovskite growth rate. By optimizing the printing process and crystallization condition, 1 µm perovskite dot arrays are EHD printed; this is, to the best of knowledge, the smallest printed feature size of perovskite application. And the photodetector still achieves high R and D * values of 14.97 A W ‐1 and 1.41 × 10 12 Jones, respectively. Finally, an integrated flexible full‐color image photodetector is constructed, which successfully realizes light signal detection and color recognition, paving a versatile and competitive approach for future full‐color image sensors and artificial vision systems. Abstract : Direct full‐color image photodetectors have considerable advantages in electronic eyes and wearable sensors. Here, electrohydrodynamic (EHD) printing of an ionic‐liquid‐based ink is first introduced to realize 1 µm perovskite dot arrays, high‐performance photodetectors ( R and D * values are 14.97 A W –1 and 1.41 × 10 12 Jones, respectively), and flexible pixelized full‐color image sensors, proving the superiority of EHD printing in perovskite optoelectronics fabrication.